ANALISIS KEBIJAKAN PABRIK GULA CANDI BARU TERHADAP DAMPAK PENCEMARAN LIMBAH PABRIK GULA (Studi kasus di Kelurahan Candi Kecamatan Candi Kota Sidoarjo) - Safarulloh, Abdus Salam (JURNAL LEGISIA, 2021)
Environmental Processing, aims to anticipate the destruction of natural effects of human activities. Natural damage can be caused due to pollution, at one time there were three officials who were arrested because of a pollution case with complaint number 012/Li-1/x/2018/, because there were victims who died, bagaimana the policy of the Candi sugar factory above environmental pollution of the community Temple village, this research uses the normatif empirical research method with a qualitative descriptive approach method, the Candi Baru Sugar Factory takes an approach with an out-of-court settlement based on the word agreement, (consensus) carried out by the parties to the dispute , The New Temple Sugar Factory makes policies for the temple village community such as, free mass circumcision, free medical treatment, distribution of basic necessities, opening up job opportunities for truck drivers, electricity costs for places of worship borne by the New Temple Sugar Factory, and also most employees of the New Temple Sugar Factory are indigenous people. Keywords : environmental pollution , out-of-court settlement, policy.